A study of radio frequency spectrum emitted by high energy air showers with LOFAR - Rossetto, Laura; Bonardi, Antonio; Buitink, Stijn; Corstanje, Arthur; Enriquez, J. Emilio; Falcke, Heino; Hörandel, Jörg R.; Mitra, Pragati; Mulrey, Katie; Nelles, Anna; Rachen, Jörg P.; Schellart, Pim; et al. (EPJ Web of Conferences, 2017)
The high number density of radio antennas at the LOFAR core in Northern Netherlands allows to detect radio signals emitted by cosmic ray induced air showers, and to characterize the geometry of the observed cascade in a detailed way. We present here a study of the radio frequency spectrum in the 30 - 80 MHz regime, and its correlation with some geometrical parameters of the extensive air shower. An important goal of this study is to find a correlation between the frequency spectrum and the primary particle type. Preliminary results on how the frequency spectrum changes as function of distance to the shower axis, and as function of primary particles mass composition are shown. The final aim of this study is to find a method to infer information of primary cosmic rays in an independent way from the well-established fluorescence and surface detector techniques, in view of affirming the radio detection technique as reliable method for the study of high energy cosmic rays.
CRIS-Team Scopus Importer:2023-08-15